Impact of web application universal design on accessibility and usability - Daniel Strzelecki; Kamil Adamiec; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute, 2025)
The aim of the paper is to analyze the usability of user interfaces of websites for sharing student notes from the perspective of universal design. The analysis aimed to verify the impact of applying universal design principles on the usability of these services. The study was conducted on two websites: the existing notatki-studenckie.pl and its counterpart created by the authors for the purpose of this study. The following research methods were used in the analysis: SUS questionnaire, an eye tracking experiment, and the WAVE validator test. The study involved two research groups, total of 34 participants. The first group, consisting of 14 computer science students, participated in the eye tracking experiment, while the second group, diverse in terms of age and technological proficiency, tested both services and completed the SUS questionnaire. The analysis of the results showed that implementing universal design principles significantly improves the accessibility and the usability of applications.